A 5 YEAR RETROSPECTIVE REVIEW OF PATIENTS WITH RENAL TRAUMA: A SINGLE CENTRE STUDY. - SEHGAL, SAJAN; Gowda, Amruthraj G; Vijayakumar. R,; Dharwadkar, Sachin; Ravikumar Br,; Mashook, Abdul Khader (Student's Journal of Health Research Africa, 2025)
Background Operative and non-operative approaches are the management options for renal trauma based on the clinical profile of the patient. This study evaluated the clinico-radiological profile of renal trauma patients (Grades I-V) and their management to determine the association of grade of renal trauma with length of hospital stay and type of treatment. Materials and Methods This retrospective cohort study was conducted in the Department of Urology, JSS Hospital, Mysuru, from January 2019 to January 2024 on patients with confirmed renal trauma on computed tomography. Results A total of 48 patients with renal trauma were included in this study. The mean age was 34 years, and the majority of the patients were males (83%). Blunt trauma was most frequently reported, and only 10% patients required surgical exploration. The distribution of patients according to grades of renal trauma was (27.1%) Grade 1;(14.6%) Grade II; (37.5 %), Grade III; (16.7 %) Grade IV; and (4.2 %) Grade V. Liver injury was the most common associated injury, followed by rib fractures and DJ stenting (12.5%) was the commonly performed surgical intervention. The mean length of hospital stay ranged from 04 to 60 days, positively correlated with the severity of grades. Microscopic hematuria was the most common presentation, with death occurring in only 3 patients of Grade V injury. Conclusion Conservative management is the preferred choice in the majority of renal trauma cases. This study has shown high renal preservation in low-grade (I-III) renal injuries, which were managed conservatively. However, surgical intervention in high-grade (IV, V) hemodynamically unstable patients was still a need.